Cambodia : Staff Report for the 2013 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Debt Sustainability Analysis update highlights Cambodia's continued low debt distress rating: all debt burden indicators are projected to remain below the respective thresholds. The authorities have made progress in monitoring their potential contingent liabilities and strengthening debt management. Consistent with the Debt Management Strategy adopted in 2012, there has been progress in monitoring potential contingent liabilities, including those related to power generation and distribution projects under public-private partnerships that receive government guarantees. The latest estimates show that the total investment of all projects amounted to about USD 3.2 billion (about 25 percent of GDP in 2012), lower than the previous estimate of about 50 percent of GDP in 2011.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet